Reaching Across the Divide (RAD): Aboriginal Elders and Academics working together to improve student and staff cultural capability outcomes - Hansen, Louise; Hansen, Percy; Corbett, Joanna; Hendrick, Antonia; Marchant, Trudi (The Australian Journal of Indigenous Education, 2020)
Abstract This article, written by Aboriginal Nyoongar Elders, Louise and Percy Hansen and Joanna Corbett in collaboration with two Wadjella (white) academics, details the design and delivery of The Reaching Across the Divide: Aboriginal Elders and Academics working together project (RAD) which aimed to develop student cultural capabilities. It is encouraging that many Australian universities aim at embedding Indigenous ways of knowing, being and doing yet there remains little information on how to do this. RAD, guided by a Nyoongar framework for engagement, the Minditj Kaart-Moorditj Kaart Framework, provides one example. RAD developed student and staff capabilities, through building trusting, committed relationships, and promoting systems change. The results highlight how co-creating to embed Indigenous pedagogy through yarning and oral storying (Hansen & Corbett, 2017; Hansen, 2017) produces transformative learning outcomes which also meet key national, local and professional directives.